MAPPING THE RESEARCH LANDSCAPE OF TOURISM VILLAGES BRANDING: A BIBLIOMETRIC ANALYSIS - Assyifa Maulida; Uud Wahyudin; Gumgum Gumilar; Yanti Setianti (Jurnal Belantara, 2026)
Tourism village integrate natural beauty, cultural heritage, and local traditions, requiring strategic and distinctive branding to enhance their appeal to both domestic and international tourists. This study aims to map the research landscape of tourism village branding through a bibliometric analysis of scientific publications indexed in Scopus from 1995 to 2024. A total of 300 documents were initially identified, which were reduced to 208 after data cleaning. The final dataset was analysed and visualised using Bibliometrix-Biblioshiny and VOSviewer to examine research performance and science mapping. This study explores trends in publication and citation growth, most influential journals and authors, citation metrics, and distribution patterns based on Bradford’s and Lotka’s Laws. Science mapping includes three-field plot visualisation, thematic evolution, conceptual structure networks, research positioning, overlay visualisation, and density mapping. The results reveal a steady increase in scholarly attention, particularly in areas concerning sustainability, destination image, and digital branding approaches. However, gaps remain in topics such as marketing communication and tourism village branding integration, indicating the need for further exploration. This study concludes that the field holds significant research potential, especially in strengthening global collaboration and integrating digital strategies into tourism village branding. The findings offer practical insights for academics and practitioners in developing more impactful and sustainable branding initiatives.